2022
DOI: 10.3389/fimmu.2022.942640
|View full text |Cite
|
Sign up to set email alerts
|

GAS6/TAM signaling pathway controls MICA expression in multiple myeloma cells

Abstract: NKG2D ligands play a relevant role in Natural Killer (NK) cell -mediated immune surveillance of multiple myeloma (MM). Different levels of regulation control the expression of these molecules at cell surface. A number of oncogenic proteins and miRNAs act as negative regulators of NKG2D ligand transcription and translation, but the molecular mechanisms sustaining their basal expression in MM cells remain poorly understood. Here, we evaluated the role of the growth arrest specific 6 (GAS6)/TAM signaling pathway … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…A more recent study showed that major histocompatibility complex (MHC) class I chain-related protein A (MICA), a cell surface ligand for NKG2D mediating natural killer (NK) cell response, is regulated by the GAS6-TAM receptor axis in MM cells. The authors proved that GAS6, secreted by bone marrow stromal cells, activated AXL and MERTK signaling, which promoted MICA expression in myeloma cells via the NF-kB pathway [ 126 ]. Another study observed a correlation between the increased frequency of M2 macrophages expressing MERTK and elevated CXCL13 levels in the bone marrow of MM patients.…”
Section: Tam Receptors In Primary Malignant Bone Tumors and Cancer Bo...mentioning
confidence: 99%
“…A more recent study showed that major histocompatibility complex (MHC) class I chain-related protein A (MICA), a cell surface ligand for NKG2D mediating natural killer (NK) cell response, is regulated by the GAS6-TAM receptor axis in MM cells. The authors proved that GAS6, secreted by bone marrow stromal cells, activated AXL and MERTK signaling, which promoted MICA expression in myeloma cells via the NF-kB pathway [ 126 ]. Another study observed a correlation between the increased frequency of M2 macrophages expressing MERTK and elevated CXCL13 levels in the bone marrow of MM patients.…”
Section: Tam Receptors In Primary Malignant Bone Tumors and Cancer Bo...mentioning
confidence: 99%